Assessment of Pulmonary Function before and after Sinus Surgery in Lung Transplant Recipients - Ramos, Bernardo Faria; Pinna, Fábio de Rezende; Campos, Silvia Vidal; Afonso Júnior, José Eduardo; Teixeira, Ricardo Henrique de Oliveira Braga; Carraro, Rafael Medeiros; Voegels, Richard Louis (International Archives of Otorhinolaryngology, 2018)
Introduction The association between sinus and lung diseases is well known. However, there are scarce studies regarding the effects of sinus surgery on pulmonary function in lung transplant recipients. The present study describes our experience with sinus surgery in lung transplant recipients with chronic rhinosinusitis.Objectives To assess the impact of sinus surgery for chronic rhinosinusitis on pulmonary function and on inpatient hospitalization days due to lower respiratory tract infection in lung transplant recipients.Methods A retrospective study conducted between 2006 and 2012 on a sample of lung transplant recipients undergoing sinus surgery for chronic rhinosinusitis. Pulmonary function, measured by forced vital capacity (FVC) and forced expiratory volume in the first second (FEV1), as well as inpatient hospitalization days due to lower respiratory tract infection, were compared 6 months before and 6 months after sinus surgery.Results The FEV1 values increased significantly, and the inpatient hospitalization days due to bronchopneumonia decreased significantly 6 months after sinus surgery. The preoperative and postoperative median FEV1 values were 2.35 and 2.68 respectively (p = 0.0056). The median number of inpatient hospitalization days due to bronchopneumonia 6 months before and 6 months after surgery were 32.82 and 5.41 respectively (p = 0.0013).Conclusion In this sample of lung transplant recipients with chronic rhinosinusitis, sinus surgery led to an improvement in pulmonary function and a decrease in inpatient hospitalization days due to bronchopneumonia.
Keywords: lung transplantation; respiratory function tests; respiratory tract diseases; paranasal sinus diseases; nasal surgical procedures